SINERGITAS PEMERINTAH DESA ADAT KUTA DAN STAKEHOLDER PT. COCA – COLA AMATIL INDONESIA DALAM PROGRAM BALI BEACH CLEAN UP (BBCU) (STUDI KASUS BBCU PANTAI KUTA) - Agustini, Putu Dian; Yasintha, Putu Nomy; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2021)
Badung Regency in the top five of having the highest waste generation in Bali,. After seeing this, PT. Coca - Cola Amatil Indonesia took the initiative to help the government and the community in overcoming the hygiene problems on several beaches in Bali, such as the one in Kuta beach, in the Bali Beach Clean Up program. PT. Coca - Cola Amatil Indonesia asks the Traditional Villages of Kuta to collaborate with them in the Bali Beach Clean Up program by cleaning up Kuta Beach. The aim of this research was to determine the synergy between the traditional villages of Kuta and PT. Coca-Cola Amatil Indonesia in enforcing the Bali Beach Clean Up campaign on Kuta Beach. These deficiencies are largely due to human and financial resource problems and lack of supervision during the activities. Keywords: Synergy, BBCU, Stakeholder, Kuta Beach